Experiencias traumáticas y trastornos de la conducta alimentaria en adolescentes y adultos - Guerrero Castro, Juan Francisco Javier (2024)
Eating disorders (EDs), which are characterized by symptoms associated with eating such as food restriction or excessive food intake; and traumatic experiences (TE) which are adverse experiences perceived as particularly transgressive, are frequently reported multi-causal phenomena, being of great relevance for mental health and clinical psychology. The present applied review aimed to identify the relationship between both psychological variables, in adolescent and adult population. Consequently, a review of the Scopus, Web of Science and SpringerLink databases was carried out, selecting 10 empirical articles that met the inclusion and exclusion criteria. The results indicate that there is a relationship between both variables, specifically, the literature relates TEs to the development of eating disorders symptomatology related to purging and binging, and even more when it comes to traumatic experiences of a sexual nature. On the other hand, it is noted that the relationship would be mediated and/or moderated by other psychological variables such as emotional dysregulation, dissociation and PTSD. According to this, further research is recommended in national and Latin American contexts, to deepen the insight of the problem and promote greater mental health.